Políticas públicas e reorganização do espaço rural: a inserção da comunidade da Sapucaia no Programa Nacional de Alimentação Escolar no município de Santo Antônio de Jesus - Ba - Santos, Joelia Silva dos (2016)
The rural reorganization stems from the actions carried out by different actors with specific interests and goals. In this sense, the state is one of the agents, together with farmers, associations, trade unions, social movements, whose actions cause repercussions in various dimensions of rural from the moment that institutionalizes and implements public policy. By Law No. 11.947 / 2009, the Brazilian State undertook to states and municipalities the obligation intended, at least 30% of funds transferred by the National Fund for Education Development (ENDF), to purchase the small farmer products and their organizations that will be used for School Feeding. The insertion of the small farmer in the National School Feeding Programme (PNAE), as supplier of agricultural genres, is a Brazilian state action geared specifically for rural segments most vulnerable by the import substitution industrialization process. In Santo Antonio de Jesus, Community Sapucaia, through the Association of farmers, sought means of insertion in the program, achieving the feat in 2014 and 2015. The repercussions of this action have resized the objects and actions systems to the point of occasioning a productive reorganization of rural properties inserted in the PNAE. This finding was obtained from this research that aimed to analyze the spatial organization of farms of small farmers in the Sapucaia community from the insertion of the Association in the PNAE in Santo Antonio de Jesus, Bahia. It is considered that the inclusion in the program allows farmers to market their products for a value consistent with the market, decreases the middleman role of action, ensures a fixed income per year and contributes to the enhancement of local agriculture